2016
DOI: 10.1063/1.4941390
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic generation in composites: Theoretical and numerical analyses

Abstract: Second harmonic generation in a transversely isotropic plate and a symmetric composite laminate is analyzed from a theoretical perspective. The strain energy function for a nonlinear elastic transversely isotropic material is expressed in terms of the five invariants of the Green-Lagrange strain tensor. Internal resonance conditions for the generation of cumulative second harmonics indicate that a cumulative second harmonic exists when the primary-secondary mode pair satisfies the phase matching and non-zero p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Early developments on the use of the higher harmonics generated by CAN focused on determining the existence of the defects in the structures. In recent years, significant progress has been made towards using higher harmonic guided waves for damage detection, which demonstrated the feasibility of using them for detecting plastic strain, fatigue damage, micro-cracking and other types of material damages [44][45][46][47][48][49][50].…”
Section: Damage Detection Using Nonlinear Guided Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early developments on the use of the higher harmonics generated by CAN focused on determining the existence of the defects in the structures. In recent years, significant progress has been made towards using higher harmonic guided waves for damage detection, which demonstrated the feasibility of using them for detecting plastic strain, fatigue damage, micro-cracking and other types of material damages [44][45][46][47][48][49][50].…”
Section: Damage Detection Using Nonlinear Guided Wavesmentioning
confidence: 99%
“…They showed that the relative acoustic nonlinearity parameter increases proportionally with the wave propagation distance due to the geometric and materials nonlinearities. Zhao et al [48] studied the second harmonic generation of Lamb waves in transversely isotropic plate and a symmetric composite laminate. They showed that for transversely isotropic plate, when waves propagate along material principal directions, the symmetric second harmonic Lamblike waves modes can be generated whereas for propagation direction other than material principal direction only the symmetric second harmonic waves are generated.…”
Section: Damage Detection Using Nonlinear Guided Wavesmentioning
confidence: 99%
“…Their results indicated that the efficiency of second harmonic generation is closely dependent on the interfacial properties. Zhao et al [39] investigated the second harmonic generation in composites and indicated that the phase matching and nonzero power flux criteria are necessary conditions for cumulative second harmonic existence, and only symmetric modes can be generated as cumulative second harmonics for symmetric composite laminates, regardless of the propagation direction of the primary mode.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on second-harmonic generation have been experimentally and computationally validated for inspecting microstructural damage, dislocations and persistent slips bands, as a function of plastic strain, fatigue life/cycle and propagating distance in metallic materials [8,[14][15][16][17][20][21][22][23][31][32][33]. More recent studies have investigated second-harmonic generations in composite structures [34][35][36] and cumulative third-and higher-order harmonics [6,7,37]. Furthermore, comprehensive reviews by Matlack et al [38] and Chillara and Lissenden [39] have summarized previous decades of work on the theoretical, experimental, and computational studies on nonlinear cumulative higher-order waves for nondestructive evaluation (NDE).…”
Section: Introductionmentioning
confidence: 99%